Elephant use and conflict leads to Tanzania’s first wildlife conservation corridor - Kikoti, Alfred; Griffin, Curtice; Pamphil, Lee (Pachyderm, 2010)
Corridors linking protected areas are recommended for reducing the effects of human settlements that fragment African elephant (Loxodonta africana) home ranges and dispersal areas, and increase human-elephant conflicts. Community interviews and hilltop surveys were used in two Maasai villages in northern Tanzania in 2000 and 2001 to determine the extent of wildlife conflict, community attitudes towards elephants, and if elephants were using a vegetation corridor between the two villages to move between Tanzania and southern Kenya. Elephants were the most problematic species in the two villages adjacent to the corridor due to crop-raiding of primarily maize (Zea mays) and beans (Phaseolus vulgaris). Although villagers considered elephants a nuisance, they believed they attracted tourists, and generally did not believe elephant numbers should be reduced. Elephants used the corridor primarily in the wet and early dry seasons, and breeding herds were more numerous than bull herds. Based upon elephant conflict and use, and the communities’ need to maintain areas for cattle grazing and medicinal plant collection, the two Maasai communities established the first wildlife conservation corridor in Tanzania working in co-operation with government authorities and other stakeholders. Key words: Amboseli, community interviews, crop-raiding, hilltop surveys, human-elephant conflict, Kilimanjaro, transboundary movements Les corridors reliant les aires protégées sont recommandés pour réduire les effets des peuplements humains qui fragmentent le domaine vital et les zones de dispersion de l’éléphant d’Afrique (Loxodonta africana), et augmentent les conflits hommes-éléphants. On a utilisé des interviews dans les communautés et des études à partir des collines chez les Maasai habitant deux villages au nord de la Tanzanie en 2000 et 2001 pour déterminer l’étendue des conflits avec la faune sauvage, les attitudes des communautés envers les éléphants, et si les éléphants utilisaient un corridor de végétation entre les deux villages pour se déplacer entre la Tanzanie et le sud du Kenya. Les éléphants étaient l‘espèce la plus problématique dans les deux villages adjacents au corridor à cause de la maraude des cultures, surtout de maïs (Zea mays) et de haricots (Phaseolus vulgaris). Bien que les villageois considèrent les éléphants comme une nuisance, ils croient qu’ils attirent les touristes, et en général ils ne croient pas que le nombre d’éléphants devrait être réduit. Les éléphants utilisaient le corridor principalement pendant la saison des pluies et au début de la saison sèche, et les troupeaux familiaux étaient plus nombreux que ceux des mâles. En se basant sur les conflits avec les éléphants et la nécessité des communautés de conserver les zones de pâturage et de collecte deplantes médicinales, les deux communautés Maasai ont créé le premier corridor pour la conservation de la faune en Tanzanie en collaboration avec les autorités gouvernementales et d’autres intervenants.